(untitled) (African Journal of Biomedical Research, 2024)
Nanoparticles are particles of less than 100 nm in diameter that exhibit new or enhanced size-dependent properties compared with bigger particles of similar material. In this study, AgNPs were synthesized using three mushroom species- Lentinus squarrosulus, Ganoderma lucidum and Pleurotus tuber-regium. The formation of AgNPs was observed using UV-light spectrophotometer. The functional groups present were identified by Fourier transform infrared spectroscopy; while size and surface morphology were also analyzed using scanning electron microscopy. The study revealed that the AgNPs were highly aggregated crystalline spherical nanoparticles with most of them irregular in shape. The cubic structure of AgNPs were identified using the X-ray Diffraction analysis with peaks for Lentinus squarrosulus at 2θ = 28.5o and 21.8o , 8o and 44o for Ganoderma lucidum, and 39o and 26o for Pleurotus tuberregium (corresponding to the planes of silver 111, 200 respectively). Antibacterial analyses from the three mushrooms showed that the biosynthesized AgNPs possess antibacterial activity (against Staphylococcus aureus, Escherichia coli, Bacillus sp, Pseudomonas aeruginosa). The antibacterial activities for each mushroom species was compared with three antibiotics- Chloramphenicol, Ciprofloxacin and Streptomycin. Th study revealed that the AgNPs of Pleurotus tuber-regium exhibited a broader antibacterial activity compared to the Lentinus squarrosulus and Ganoderma lucidum